Determinants for the intention to adopt enterprise risk management among small and medium enterprises (SMEs) / Siti Musliha Mohd Idris - Mohd Idris, Siti Musliha (2017)
The importance of small and medium enterprises has been recognized by most developing countries. This is due to their contribution to the national economy and employment opportunities including Malaysia. However, in their rapid establishment, they are still facing the problem of weakening and failure at almost 42% in Malaysia. In this modern day of environment, either large companies or SMEs also have challenges and weaknesses. In order to sustain and survive in contributing to the economy of the country, risk management or enterprise risk management (ERM) has been seen as a tool that could help SMEs to grow and to survive in a global market. ERM is not new in Malaysia as it has been adopted by many large corporations and financial institutions but for SMEs, ERM is a new thing that needs to be explored and understood. The study of ERM adoption has been increasing in recent years but for SMEs, it is still sparse. In view of this, the purpose of this study is to discover the determinants of intention to adopt ERM by manufacturing SMEs. The conceptual framework of this study was built form the fundamental understanding on ERM determinants intention to adopt, theories form the combination of DTOE, TOE and IDT model which comprises of selected demographic profile, decision-maker, organizational and external environment. This study model posited on firm size, firm age, firm sector, top management support, presence of Chief Risk Officer (CRO), firm complexity, ownership structure, regulatory pressure and competitive pressure. From the questionnaire survey, 160 responses had been analyzed using the Statistical Package of Social Science (SPSS) 22.0. The findings revealed that intention to adopt ERM by SMEs was influenced by the regulatory pressure and competitive pressure. Next, the intention also driven by the presence of CRO, firm complexity and ownership structure. Surprisingly, top management support had no significant effect on the intention to adopt ERM in SMEs and this could be due to lack of knowledge on ERM benefits and the newness of ERM in SMEs industry. A competent study of SMEs is able to provide an understanding and additional knowledge on the ERM in SME for the practitioners and academician. The discussion and implication provided in this study would strengthen the body of knowledge on the ERM intention to adopt and adoption which affects the SMEs business performance, besides acting as a reference for empirical research.